Effects of chromium picolinate on reproduction and farrowing performance of parity one sows - Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
We examined the influence ofchromium picolinate fed to gilts during the growing phase from 50 Ib through their first farrowing on reproductive and farrowing performance. No differences were detected in first service farrowing rate or total or live born litter size. These datafail to support a positive influence of chromium picolinate fed during development and gestation on reproductive and farrowing performance ofparity 1 sows.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Sows; Chromium picolinate; Litter size; Gilt development